P–313 Endometrial receptivity analysis for personalized embryo transfer in patients with recurrent implantation failure: a retrospective analysis of a Chinese cohort. (6th August 2021) - Jia, Y; Sha, Y L; Qiu, Z; Guo, Y H; Tan, A X; Huang, Y; Zhong, Y; Dong, Y J; Ye, H X
Abstract: Study question: To quantify the effectiveness of endometrial receptivity analysis (ERA)-guided personalized embryo transfer (pET) in Chinese women. Summary answer: ERA-guided pET may remarkably improve pregnancy and implantation rates among Chinese women with Recurrent implantation failure (RIF). What is known already: RIF is a major cause of infertility, and endometrial receptivity is widely accepted to impact implantation failure. Precision prediction of the WOI, the time when the endometrium is most receptive to the implantation of the embryo, is, therefore, of great significance to improve implantation prospects. Previous studies have shown the effectiveness of ERA for the prediction of the WOI, and how pET, timed by ERA, improves implantation and pregnancy rates; however, the efficacy of ERA-guided pET remains unknown for Chinese women. Study design, size, duration: Patients in Chengdu Xi'nan Gynecology Hospital (Chengdu, China) who were undergoing frozen embryo transfer (FET) at the blastocyst stage on day five or day six during the period from November 2019 through September 2020 were recruited for this study. A total of 145 eligible patients were included in the study and assigned to the ERA group (n = 67) or the control group (n = 78). Clinical pregnancy outcomes were compared between the two groups. Participants/materials, setting, methods: Endometrial specimens were collected the from ERA group. Total RNA was extracted from endometrial specimens, the transcriptomic sequencing data were processed using RNA-Seq and the endometrial receptivity status was assessed by the ERA predictor. The endometrium was classified as receptive or non-receptive according to the ERA assessment, and pET was done at the time determined by ERA in the ERA group. Subjects in the control group did not receive ERA and underwent blastocyst transfer normally. Main results and the role of chance: The demographic and clinical characteristics were comparable between the ERA and control groups (P > 0.05). The ERA test identified 10.45% of samples as receptive and 89.55% of samples as non-receptive in the ERA group, with 70.15% of samples presenting a pre-receptive profile. We observed higher cumulative pregnancy (74.63% vs. 64.10%) and cumulative implantation rate (47.32% vs. 21.68%) rates, and a lower biochemical pregnancy rate (18.00% vs. 34.00%) in the ERA group when compared to the control group (P < 0.05). Additionally, we found higher pregnancy (67.16% vs. 39.74%) and implantation (46.54% vs. 16.94%) rates as well as a lower biochemical pregnancy rate (17.78% vs. 45.16%) after the first ERA test in the ERA group when compared to the control group (P < 0.01). Limitations, reasons for caution: First, this is a retrospective analysis, which is relatively more biased than prospective clinical trials. Second, the study sample is considerably small. Third, only 10.45% of the subjects were identified as presenting a receptive profile, which limits the comparisons of clinical outcomes between patients with receptive and non-receptive endometria. Wider implications of the findings: This study demonstrates that the ERA test helps to determine the optimal timing for embryo transfer, improve pregnancy and implantation rates in patients with RIF, and guides the clinical application of the ERA test. Trial registration number: approval No. 2020–018